THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZED LEARNING - Kanta, Siddappa M (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The integration of Artificial Intelligence (AI) into personalized learning represents a transformative shift in the educational landscape. Traditional educational methods often follow a one-size-fits-all approach, which fails to accommodate the diverse learning needs, paces, and styles of individual students. AI, with its ability to analyze vast amounts of data, offers tailored learning experiences that adapt to the unique requirements of each learner. This paper explores the role of AI in personalized learning, highlighting its potential to enhance student engagement, improve learning outcomes, and provide real-time feedback. AI technologies, such as machine learning algorithms, natural language processing, and data analytics, empower educational platforms to offer customized learning paths. These platforms track student interactions, assess their strengths and weaknesses, and adjust content delivery to match their learning pace and preferences. By providing instant, targeted feedback and continuously evolving learning materials, AI ensures that students are neither overwhelmed nor under-challenged, fostering a more effective and efficient learning environment. Furthermore, AI enables educators to offer more personalized attention to students by automating administrative tasks and providing insightful data on individual performance. This frees up valuable time for teachers to focus on meaningful interactions with students. AI also contributes to educational inclusivity by making learning resources accessible to a wider audience, overcoming barriers such as geographic location, language, and socioeconomic status. While the potential benefits of AI in personalized learning are immense, challenges such as data privacy, algorithmic bias, and the need for technological infrastructure must be addressed. This paper concludes by emphasizing the need for ethical considerations and collaborative efforts to maximize AI’s impact on creating a more inclusive, equitable, and effective education system.